The Creating Sustainability Through Talent Management Improvement: A Case of Sekolah Tinggi Manajemen IPMI - Fadhillah Indra Budi (Sekolah Tinggi Manajemen IPMI, 2022)
In this fast changing era, where every institutions organization should be adapted in order to be survived, MBA students of IPMI International Business School were conducting research about IPMI organization itself and share their findings and recommendation in order not only to be survive, but also to be competitive with other educational institutions.